Plasma proteomic signatures of enteric permeability among hospitalized and community children in Kenya and Pakistan - Kirkby D. Tickell; Donna M. Denno; Ali Saleem; Zaubina Kazi; Benson O. Singa; Catherine Achieng; Charles Mutinda; Barbra A. Richardson; Kristjana H. Ásbjörnsdóttir; Stephen E. Hawes; James A. Berkley; Judd L. Walson (iScience, 2023)
Summary: We aimed to establish if enteric permeability was associated with similar biological processes in children recovering from hospitalization and relatively healthy children in the community. Extreme gradient boosted models predicting the lactulose-rhamnose ratio (LRR), a biomarker of enteric permeability, using 7,500 plasma proteins and 34 fecal biomarkers of enteric infection among 89 hospitalized and 60 community children aged 2–23 months were built. The R2 values were calculated in test sets. The models performed better among community children (R2: 0.27 [min-max: 0.19, 0.53]) than hospitalized children (R2: 0.07 [min-max: 0.03, 0.11]). In the community, LRR was associated with biomarkers of humoral antimicrobial and cellular lipopolysaccharide responses and inversely associated with anti-inflammatory and innate immunological responses. Among hospitalized children, the selected biomarkers had few shared functions. This suggests enteric permeability among community children was associated with a host response to pathogens, but this association was not observed among hospitalized children.